The Coach's Role in Understanding the Athletes' Condition: Maximizing Communication Functions - Eko Purnomo; Siti Aisyah; Hartono Hadjarati; Adek Cerah Kurnia Azis; I Kadek Suardika; Nina Jermaina; Nurkhoiroh Nurkhoiroh; Agus Gumilar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The coach relationship is one of the keys to success for an athlete. This relationship will be good if each person has the communication skills to accept and understand each other. This research aims to explore the role of a coach in understanding an athlete's condition in order to maximize the role of communication in that relationship. To conduct this research on the coach's role in understanding athletes' condition and maximizing communication functions, a selective study approach will be employed. The research sample was 173 (124 men, 49 women) from various sports (accuracy; martial arts; games; measurable) who participated in this research. The average age of participants was 20.07. The research results obtained were then analyzed using simple linear regression. This research uses the Coach Confirmation Instrument (CFI) with a value of α = 0.95. The calculation results of the three data (gender, sports involvement and type of sport) obtained a value of > 0.05, which means there is no significant relationship between gender, sports involvement and type of sport on coach confirmation. This means that gender has no impact on coach confirmation. Likewise with sports involvement and type of sport on coach confirmation. The conclusion of this research is that the coach's communication skills play an important role in understanding the athlete's condition, regardless of gender (male; female), sports involvement (individual; team), type of sport (accuracy; martial arts; games; measurable).